Quantitative Easing and Exuberance in Government Bond Markets: Evidence from the ECB's Expanded Assets Purchase Program - Martijn Droes; Ryan van Lamoen; Simona Mattheussens (Tinbergen Institute, 2017)
This paper examines whether the ECB's Quantitative Easing (QE) policy is causing government bond prices to deviate from their fundamental value. We use a recent advance in the methodology to measure exuberant price behavior in financial time series introduced by Phillips et al. (2015). We extend this methodology and apply it to government bond prices. The results show that the QE policy substantially inflated government bond prices in Euro Area countries to such an extent that bond prices are no longer in line with the underlying fundamental value. We argue that careful monitoring is required when the QE policy is eventually reversed. The test procedure outlined in this paper provides a monitoring tool to do so.
Keywords: G12; G15; E52; 330; government bond yields; asset price bubbles; monetary policy